A 4-quadrant framework on strategy, community, learning and innovation for the application of knowledge management in public sector organisations in construction / Khairil Hizar Md Khuzaimah - Md Khuzaimah, Khairil Hizar (2017)
Recognising the pivotal role played by knowledge management in today's challenging environment, many public organisations have begun to embrace the discipline as part of their key strategic management tools in pursuit of attaining high performance and organisational excellence. Nevertheless, despite the emerging interest from various public organisations, coupled with concerted efforts by the government to encourage the application of knowledge management in the public sector, the uptake is still relatively low and most concernedly, the success rate is very minimal. Research reveals that this is largely attributed to the inherent characteristics that are highly unique to public organisations which are extremely rigid and hierarchical in structure and further aggravated by their bureaucratic-laden procedures. As such, the process of formally managing knowledge can be a very challenging endeavour for the public sector. The research aims to develop a knowledge management framework to aid effective knowledge management implementation in Malaysian's public sector organisations involved in construction towards providing outstanding services to their stakeholders in terms of project delivery and project management services. In operationalising the research process, an embedded mixed method research design was adopted, spread into three main phases. The first phase consisted of four main activities; literature review, pilot interview, the establishment of research aim and the development of the research objectives while the second phase involved six main activities including the development of the conceptual framework, identification and establishment of research methodology, data collection 1 (quantitative - selfadministered online questionnaire survey), data analysis 1 (quantitative), data collection 2 (qualitative - semi-structured interview) and data analysis 2 (qualitative). As for the final phase of the research, it comprised of summary of the findings and the preparation of the final research report. Findings from the research reveal that knowledge management is quintessentially multifaceted, encompassing various key organisational elements which can be categorised into six primary categories; Strategy and Governance, Community, Learning, Innovation, Information Technology and Common Shared Values. Following this, a conceptual knowledge management framework which dynamically integrates all the critical organisational elements was developed, deliberately intended to serve as a sound basis for public sector organisations involved in construction in implementing effective knowledge management initiatives. These findings add to a growing body of literature on knowledge management in public sector. In addition, the proposed framework offers a viable solution for public sector organisations involved in construction in better managing their organisational and technical knowledge systematically.